Pharyngeal gonorrhoea in men who have sex with men. (April 2020) - Richardson, Daniel; Pickering, Alice; Trotman, Daniel; Nichols, Kayleigh; Buss, Zoe; Devlin, John; Finnerty, Fionnuala
Pharyngeal gonorrhoea is important in the transmission dynamics of gonorrhoea, and generation of antimicrobial resistance and the performing of culture remains vital. We reviewed the notes of men who have sex with men (MSM) presenting to our clinic with a positive pharyngeal NAAT for gonorrhoea between January and December 2019. There were 383 cases of NAAT-positive pharyngeal gonorrhoea, and 28 (7%, 95% CI = 5.11–10.36) reported sore throat at presentation. Pharyngeal cultures were taken from 270/383 (70%), and 73/270 (27%) were culture positive with available antimicrobial sensitivities. Overall, the presence of pharyngeal symptoms was not associated with pharyngeal chlamydia (OR = 1.6, CI = 0.19–13.32, p = 0.7), HIV status (OR = 1.1, CI = 0.47–2.57, p = 0.8), positive cultures (OR = 1.9, CI = 0.78–4.62, p = 0.2) or age ( p = 0.3). Routine screening of MSM for pharyngeal gonorrhoea is important to maintain surveillance and measures need to be taken to improve pharyngeal culture sampling from MSM.